Determinants of Profitability in Indonesian Listed Insurance Companies - Arazi, Muhammad Ghazi Al-Ghifari; Arip, Syamsul; Muchtar, Susy (Research Horizon, 2025)
Insurance companies play a vital role in managing risk and maintaining economic stability. Understanding the factors influencing their profitability is essential for effective decision-making. This study examines the determinants of profitability among 18 insurance companies listed on the Indonesia Stock Exchange during the 2019–2023 period. Using a quantitative research design, the study analyzes 90 observations by applying panel data regression, which combines time series and cross-sectional data, supported by E-Views 9.0 software. The variables tested include company-specific factors such as age, leverage, liquidity, loss ratio, premium growth, asset tangibility, managerial efficiency, and company size, along with macroeconomic indicators like GDP growth and inflation. The regression results reveal that only managerial efficiency has a significant negative impact on profitability, as measured by Return on Assets. This indicates that lower operational efficiency is associated with reduced profitability. In contrast, variables such as company age, leverage, liquidity, loss ratio, premium growth, asset tangibility, company size, GDP growth, and inflation show no significant effect on profitability. The findings highlight the critical role of internal management efficiency over external or structural factors in driving financial performance. This research offers valuable insights for insurance company managers, emphasizing the need to improve operational efficiency to enhance profitability.